Emilia Mišćenić, Ivana Kunda, Silvija Petrić, Vlatka Butorac Malnar, Danijela Vrbljanac i Sandra Winkler EUROPSKO PRIVATNO PRAVO: POSEBNI DIO (Zbornik Pravnog fakulteta Sveučilišta u Rijeci, 2023)
Recenzija